DEMOKRASI KETUHANAN (TEISTIK) DI INDONESIA: AKTUALISASI NILAI PEMIKIRAN MOH. NATSIR - Yudi Fahrian, Yudi; Fitri, Aidil (Fakultas Hukum Universitas IBA Palembang, 2023)
Abstract Muhammad Natsir believes that the Islamic principles of shura (deliberation) are closer to modern democratic formulations. Thus Natsir can accept the existence of parliament as a representation of the implementation of these deliberations. However, as described by Muhammad Iqbal above, Natsir rejects modern democracy with a background in Western secular culture. Secularism is an understanding that separates religious issues from state issues, where this understanding comes from the West. Muhammad Natsir cannot separate his thoughts from religion and the divine values ​​he adheres to. Muhammad Natsir stated “As a Muslim, we cannot escape politics. As a politician, we cannot escape from our ideology, namely the ideology of Islam. The concept of divine democracy, commonly referred to as Theistic democracy in Indonesia, was initiated by an intellectual, preacher and politician, namely Mohammad Natsir. Until now the idea of ​​theistic democracy has never materialized. There are several problems in actualizing theistic democratic values ​​related to the concept of rule of law which are related to epistemological problems, methodological problems and political problems. The actualization of theistic democracy can be pursued through two approaches, the first is the approach with the main scientific concept of the concept of prophetic law, the second is through legislation with three stages, the formulation stage, the socialization stage and the political stage.